Effect of corneal stiffness decrease on axial length elongation in myopia determined based on a mathematical estimation model - Ren, Qi; Chu, Zhe; Cui, Wei; Cheng, Lu; Su, Wenjie; Cheng, Hao; Wu, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To investigate the relationship between the corneal material stiffness parameter stress-strain index (SSI) and axial length (AL) elongation with varying severities of myopia, based on a mathematical estimation model. Methods: This single-center, cross-sectional study included data from healthy subjects and patients preparing for refractive surgery in the Qingdao Eye Hospital of Shandong First Medical University. Data were collected from July 2021 to April 2022. First, we performed and tested an estimated AL model (AL_Morgan) based on the mathematical equation proposed by Morgan. Second, we proposed an axial increment model (ΔAL) corresponding to spherical equivalent error (SER) based on AL_emmetropia (AL_Morgan at SER = 0) and subject’s real AL. Finally, we evaluated the variations of ΔAL with SSI changes based on the mathematical estimation model. Results: We found that AL was closely associated with AL_Morgan (r = 0.91, t = 33.8, P < 0.001) with good consistency and SER was negatively associated with ΔAL (r = -0.89, t = -30.7, P < 0.001). The association of SSI with AL, AL_emmetropia, and ΔAL can be summarized using the following equations: AL=27.7-2.04×SSI, 〖AL〗_emmetropia=23.2+0.561×SSI, and ΔAL=4.52-2.6×SSI. In adjusted models, SSI was negatively associated with AL (Model 1: β = -2.01, P < 0.001) and ΔAL (Model 3: β = -2.49, P < 0.001) but positively associated with AL_emmetropia (Model 2: β = 0.48, P < 0.05). In addition, SSI was negatively associated with ΔAL among subjects with AL ≥ 26 mm (β = -1.36, P = 0.02) Conclusion: AL increased with decreasing SSI in myopia.